The genetic basis of congenital hyperinsulinism. Issue 5 (1st March 2009) - James, C; Kapoor, R R; Ismail, D; Hussain, K
Abstract : Congenital hyperinsulinism (CHI) is biochemically characterised by the dysregulated secretion of insulin from pancreatic β-cells. It is a major cause of persistent hyperinsulinaemic hypoglycaemia (HH) in the newborn and infancy period. Genetically CHI is a heterogeneous condition with mutations in seven different genes described. The genetic basis of CHI involves defects in key genes which regulate insulin secretion from β-cells. Recessive inactivating mutations in ABCC8 and KCNJ11 (which encode the two subunits of the adenosine triphosphate sensitive potassium channels (ATP sensitive KATP channels)) in β-cells are the most common cause of CHI. The other recessive form of CHI is due to mutations in HADH (encoding for-3-hydroxyacyl-coenzyme A dehydrogenase). Dominant forms of CHI are due to inactivating mutations in ABCC8 and KCNJ11, and activating mutations in GLUD1 (encoding glutamate dehydrogenase) and GCK (encoding glucokinase). Recently dominant mutations in HNF4A (encoding hepatocyte nuclear factor 4α) and SLC16A1 (encoding monocarboxylate transporter 1) have been described which lead to HH. Mutations in all these genes account for about 50% of the known causes of CHI. Histologically there are three (possibly others which have not been characterised yet) major subtypes of CHI: diffuse, focal and atypical forms. The diffuse form is inherited in an autosomal recessive (or dominant manner), the focal form being sporadic in inheritance. The diffuse form of the disease may require a near total pancreatectomy whereas the focal form requires a limited pancreatectomy potentially curing the patient. Understanding the genetic basis of CHI has not only provided novel insights into β-cell physiology but also aided in patient management and genetic counselling.